The comparison of sarcopenia prevalence, nutrition and exercises between rheumatoid arthritis patients and healthy subjects - Yamada, Mai; Furuyama, Masako; Origuchi, Tomoki (Clinical Rheumatology and Related Research, 2023)
Objective: To compare the prevalence of sarcopenia and the status of nutrition and exercises between rheumatoid arthritis（RA）patients and healthy control subjects. Subjects: Fifty-three RA patients（66.5 years old, all female）and 30 healthy controls（65.8 years old, all female）. Methods: The skeletal muscle mass index（SMI）, grip strength, 10-m walking speed, and 5-time Sit-to-Stand Test were measured, and the nutritional status（Mini Nutritional Assessment Short-Form [MNA-SF], frequency of animal protein intake）and exercise frequency and exercise contents were assessed. Results: Sarcopenia was significantly more prevalent（37.8% vs. 3.2%）and the SMI and leg muscle mass were significantly lower in the RA group than in the control group. The percentage of RA patients who did not consume animal protein at least twice a day was 54.7 %（vs. 20.0 % in the control group）. The RA group with sarcopenia was older and more undernourished than the RA group without sarcopenia, but they exercised more frequently of aerobic exercise than the control subjects, and they had received no rehabilitative guidance. Conclusions: The RA group had a higher prevalence of sarcopenia than the control group, and the low frequency of animal protein intake. RA patients with sarcopenia tended to be undernourished. Although they exercised more frequently, they received no rehabilitative guidance. This study suggests that combined intervention of nutritional guidance and exercise therapy is desirable from the early stage of RA.